2004
DOI: 10.1001/archfaci.6.2.78
|View full text |Cite
|
Sign up to set email alerts
|

The Average African American Male Face

Abstract: To determine the average facial proportions of the African American man and compare results with the neoclassical canons of facial proportions and the standard for the North American white man.Design: Cross-sectional survey.Methods: Photographs and anthropometric measurements of the face were taken of 109 men of African American descent aged between 18 and 30 years, and results were compared with the neoclassical canons of the facial proportion and the averages of the anthropometric measurements for the North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
5
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 11 publications
9
69
5
3
Order By: Relevance
“…An acute nasolabial angle (83.1 0 ) has also been reported among the African American man [7]. Reksodiputro et al [6] also recorded a smaller nasolabial angle (92.81 0 ) among the Javanese female than in the white women.…”
Section: Discussionmentioning
confidence: 88%
“…An acute nasolabial angle (83.1 0 ) has also been reported among the African American man [7]. Reksodiputro et al [6] also recorded a smaller nasolabial angle (92.81 0 ) among the Javanese female than in the white women.…”
Section: Discussionmentioning
confidence: 88%
“…Several works 10,[14][15][16][17][18]22 have anthropometrically analyzed facial features of different populations. However, discussions between those studies and the present work are somewhat difficult to make due to the notable genotypic (and thereby phenotypic) variation between races.…”
Section: Discussionmentioning
confidence: 99%
“…The average of these measurements from facial 3D images represents the facial morphology of soft tissue from adults and can be used to assist with diagnoses and the treatment regimens of patients from different countries, as it shows population's singularities and soft tissue structures 10 . Several studies have, in fact, also aimed at creating facial profiles of different racial groups [14][15][16][17][18][19] . In Brazil, such mapping of facial profiles has not been conducted, and stereophotogrammetry techniques could certainly provide accurate measurements of the populations' facial traits for comparison between the country's different regions as well as to other international studies.…”
Section: Introductionmentioning
confidence: 99%
“…11 Standard anthropometric measurements are still being used to estimate differences between the faces of different de- scents. 13 A ''mega project'' using standard anthropometric measurements showed that establishment of facial databases for various ethnic groups/races is essential. 14 Furthermore, it was shown that 3D imaging with laser scanning devices can be used reliably and with great accuracy.…”
Section: Discussionmentioning
confidence: 99%